Factors Motivating Citizen Engagement in Mobile Sensing: Insights from a Survey of Non- Participants - Leao, S.; Izadpanahi, Parisa (Routledge, 2016)
Mobile sensing uses features of mobile technology to monitor the environ- ment and if a community participates in such monitoring, there can be community improvements in the quality of life. Despite the numerous potential benefits, the rate of citizen engagement in mobile sensing is generally low. Using the urban sensing project called “2Loud?,” this study was designed to uncover the reasons for non-participation and to discuss the motivations for intention to participate. A survey was administered to citizens who had been invited to participate but had decided not to participate. Examin- ing the four motivational factors of “Concern,” “Belief,” “Technology,” and “Time” through a series of Kruskal-Wallis H Tests indicated that respondents had a statistically significant favorable attitude toward “Intention to Participate” if they had some concern and belief, and if they had access to technology and available time, compared to those who did not. However, binary logistic regression analysis indicated that only “Time” and “Technology” were significant predictors of “Intention to Participate.” These findings are discussed in light of social psychology and information technology the- ories, and recommendations for improved communication and engagement strategies are suggested.